2018
DOI: 10.1186/s12889-018-6263-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of alcohol and drug use among secondary school students in Botswana: a cross-sectional study

Abstract: BackgroundAlcohol and illicit drug use has been recognized as a growing problem among adolescents in Botswana. Little is known about factors affecting alcohol and drug use among Botswana’s secondary school students. To aid the design and implementation of effective public health interventions, we sought to determine the prevalence of alcohol and drug use in secondary school students in urban and peri-urban areas of Botswana, and to evaluate risk and protective factors for substance use.MethodsWe performed a 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 49 publications
8
32
1
1
Order By: Relevance
“…When compared to other African countries, the prevalence of harmful use of alcohol in Nigeria is relatively higher. For example, the prevalence of self-reported binge drinking was 14.1% in South Africa (16) and 16% in Ghana (17), while hazardous users of alcohol were estimated at 12.7% in Uganda (18) and 22.4% in Botswana (19). Despite a declining rate, Nigeria appears to be at the high-end of alcoholic beverage consumption in Africa, as the reported rates are comparable to some estimates in Europe and the Americas, where the prevalence of harmful users ranged from 37-53% (1,68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to other African countries, the prevalence of harmful use of alcohol in Nigeria is relatively higher. For example, the prevalence of self-reported binge drinking was 14.1% in South Africa (16) and 16% in Ghana (17), while hazardous users of alcohol were estimated at 12.7% in Uganda (18) and 22.4% in Botswana (19). Despite a declining rate, Nigeria appears to be at the high-end of alcoholic beverage consumption in Africa, as the reported rates are comparable to some estimates in Europe and the Americas, where the prevalence of harmful users ranged from 37-53% (1,68).…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the consumption of alcohol in Nigeria may provide insights into the rate of consumption in some African settings, being the most populous country on the continent. Asides few studies in some African countries (16)(17)(18)(19), there is generally limited national epidemiological studies on alcohol consumption in Africa, which appears to limit public health response and comparisons with other world regions. Across many African countries, alcohol mis(use) is less addressed, as there are no clear regulations for alcohol marketing, with this even worse in the absence of representative and up-todate epidemiologic reports on alcohol consumption (20).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant finding of substance ever use in the assessment was alcohol consumption, 157(14.0%) of students consumed alcohol followed by khat, 57 (5.1%). This was very much lower than ever use of substance in five Ethiopian universities, 25.8% [22] and Botswana 816(42.1%) students consumed alcohol [21]…”
Section: Substance Usementioning
confidence: 95%
“…Journal of Addiction significant covariates of substance use. Adolescents from schools with low commitment to control drugs and follow students more likely to use substance [44] while [45] found that there is no association with school commitment and substance use. Adolescents belong to mothers' with no education at all had a higher odds of using substance compared to those belongs to mothers of higher education.…”
mentioning
confidence: 99%